Designing a virtual laboratory for chemistry using Animated Pedagogical Agent (APA) - Ab. Halim, Haslinda; Bakar, Norasiken; Ahmad, Ibrahim; Shahbodin, Faaizah (Malaysian Educational Technology Association (META), Educational Technology Division, Ministry of Education Malaysia, 2009)
This paper presents about designing the animated pedagogical agent in virtual laboratory for chemistry subject, alcohol. The further develop and exploit this potential, there are. several issues that need to be solved. In his paper we discuss on theoretical framework modelling that is divided into five parts which is analysis, design, development, implementation and evaluation. For the second objective, researcher will view on the visual form of virtual laboratory and key aspects of look of animated pedagogical agent to make human-computer interaction more enjoyable and productive. In designing the development of virtual laboratory, researcher has used approach in learning theory such as cognitive and constructivism. Concept through learning-by-doing and simulation will be added in the virtual laboratory where through the concept used student can obtain understanding via experience.